An Exploratory Study to Understand the Difference in Personality Characteristics of Lgbtq+ And Heterosexual Individuals - Kaur, Ravjot (My University, 2023)
The study was to understand the difference in personality characteristics of LGBTQ+ and heterosexual individuals. Human figure drawing test was used as a tool to analyze the same. Sample size of 30 LGBTQ+ population and 30 heterosexual population was taken aged 18-25 years. Statistical analyses used to compute the difference was Chi square using SPSS. The results showed that there are differences in certain aspects of different personality characteristic analyzed through the drawings of individuals over different sexual orientation. Significant difference was found in features of anxiety among different sexual orientation, i.e., extreme asymmetry p<0.05 and sketching p<0.01. Significant difference was found in features of positive self-concept among different sexual orientation, i.e., large size p<0.05 and addition of extraneous objects p<0.01. No difference was found in features of negative self-concept among different sexual orientation. Significant difference was found in features of aggression among different sexual orientation, i.e., large size p<0.05, spiked fingers p<0.05 and nostrils showing p<0.05. Significant difference was found in features of sexual disturbance among different sexual orientation, i.e., disheived hair p<0.05, waist emphasis p<0.05 and nose omitted p<0.05. No difference was found in features of developmental impairment/regression among different sexual orientation except for one feature, i.e., partially clothed p<0.05.
Keywords: LGBTQ+; Heterosexual; Personality Characteristics